Training and development process of Al-Arafah Islami Bank Ltd & general banking system of Al-Arafah Islami Bank Ltd - Raka, Tasnia Jeon (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.